Sildenafil improves heart rate variability in dogs with asymptomatic myxomatous mitral valve degeneration - Prapawadee Pirintr (2018)
© 2017 The Japanese Society of Veterinary Science. Myxomatous mitral valve degeneration (MMVD) causes an imbalance of sympathovagal activity resulted in poor cardiac outcomes. Phosphodiesterase-5 inhibitors have been revealed cardioprotective effect in patients with heart diseases. This study aimed to 1) compare the heart rate variability (HRV) between asymptomatic MMVD and healthy dogs and 2) assess long-term effects of sildenafil and enalapril on time- and frequency-domains analyzes. Thirty-four dogs with MMVD stage B1 or B2 and thirteen healthy dogs were recruited into the study. MMVD dogs were divided into 3 subgroups: control (n=13), sildenafil (n=12) and enalapril (n=9). HRV was analyzed from 1-hr Holter recording at baseline (D0) in all dogs and at 30, 90 and 180 days after treatment. The results showed that MMVD dogs had significant higher heart rate (HR), systemic blood pressures, the ratio of low to high frequency (LF/HF) and had significant decreased standard deviation of all normal to normal RR intervals (SDNN) and the percentage of the number of normal-to-normal sinus RR intervals with differences > 50 msec computed over the entire recording (pNN50) when compared with healthy dogs (P < 0.05). Neither time nor frequency domain parameters were different among subgroups of MMVD dogs at D0. After treatment with sildenafil for 90 days, both time- and frequency-domain parameters were significantly increased when compared with control and enalapril groups. This study demonstrated that sildenafil improves HRV in asymptomatic MMVD dogs suggesting that sildenafil should be used in the MMVD dogs to restore the sympathovagal balance.